A comparative study of insulator materials exposed to high voltage AC and DC surface discharges - Heger, Gernot (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.